PERSONALITY DYNAMICS OF LUCAS IN THE NOVEL MIRACLE ON 5TH AVENUE BY SARAH MORGAN - Ai Asmanah; Henny Suharyati; Shita Dewi Ratih P (Universitas Pakuan, 2020)
This study examines the personality dynamics of the character, Lucas, in the novel Miracle on 5th Avenue by Sarah Morgan. The purpose of this study are: 1) Describing the character, Lucas, who experienced personality dynamics. 2) Describing the causal factors, the impact on the character and the completion of the personality dynamics of the character Lucas based on the psychoanalysis theory of Sigmund Freud. The presentation methodin this research is qualitative descriptive method, namely data analysis in the form of descriptive literature. The results of the study are described as follows: (1) Lucas is a criminal book writer whose life is suffering from being abandoned by loved ones and work pressures. (2) As a result of the causes of the conditions of his life, the personality dynamics of the character Lucas occur, starting from anxiety, life instincts (eros), and death instincts (thanatos). Anxiety comes when the anxiety and despair that are felt due to being abandoned by his beloved wife give rise to death instincts in the character Lucas to end his life. However, the presence of Eva, the character who is able to change Lucas’s life, dominated his life instincts by the id system in the form of his desire or libido towards Eva and also his efforts to survive for a better life. Keywords: Personality Dynamics, Figure, Psychoanalysis